2017
DOI: 10.1101/134494
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of initial body orientation on escape probability in prey fish escaping from predators

Abstract: Since the escape response is crucial to survival and hence to the fitness of species, several studies have attempted to elucidate the kinematic and behavioral components of the response that affect evasion outcome. The prey’s body orientation relative to a predator at the onset of the escape response (initial orientation) could affect evasion outcome, because the turn angle and its duration before the initiation of escape locomotion would be smaller when the initial orientation is more away from the predator. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Behavioral and neurobiological studies have shown that the Stage 1 turning angles are affected by stimulus direction (Domenici and Blake, 1993;Eaton and Emberley, 1991;Kimura and Kawabata, 2018). The escape response typically avoid predation when the prey evades in the direction opposite to that of the approaching predators (Walker et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Behavioral and neurobiological studies have shown that the Stage 1 turning angles are affected by stimulus direction (Domenici and Blake, 1993;Eaton and Emberley, 1991;Kimura and Kawabata, 2018). The escape response typically avoid predation when the prey evades in the direction opposite to that of the approaching predators (Walker et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, Stage 1 turning angles tend to be wide when the stimulus approaches fronting the prey and narrow when the stimulus approaches behind the prey (Domenici and Blake, 1993;Eaton and Emberley, 1991;Kimura and Kawabata, 2018). The optimal escape trajectory was suggested to be between 90° and 180° depending on predator speed (Domenici, 2002;Weihs and Webb, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…An additional acrylic divider was positioned above the aquarium (touching the water) preventing the distortions in the recorded video images due to the propagation of surface waves. As the distance between the acoustic/motion source and fish position may affect kinematics (Kimura and Kawabata, 2018), fishes were only stimulated when located about 11±2 cm from the stimulus. In addition, a fish was considered for stimulus only if its body centre of mass was at least 0.75 body lengths away from any wall and the anterior part of its body was oriented at an angle of less than 5 deg to the tank edge.…”
Section: Materials and Methods Fishmentioning
confidence: 99%